2020
DOI: 10.3390/ph13120470
|View full text |Cite
|
Sign up to set email alerts
|

Update on Chemotherapeutic Approaches and Management of Bevacizumab Usage for Glioblastoma

Abstract: Glioblastoma, the most common primary brain tumor in adults, has one of the most dismal prognoses in cancer. In 2009, bevacizumab was approved for recurrent glioblastoma in the USA. To evaluate the clinical impact of bevacizumab as a first-line drug for glioblastoma, two randomized clinical trials, AVAglio and RTOG 0825, were performed. Bevacizumab was found to improve progression-free survival (PFS) and was reported to be beneficial for maintaining patient performance status as an initial treatment. These out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 113 publications
0
10
0
Order By: Relevance
“…Accordingly, there is no robust evidence supporting the efficacy of BEV treatment for nd-GBM; however, BEV has been approved in Japan as an insurance-covered first-line drug for GBM concurrently with its second-line application, considering the benefit of maintaining patient performance status [5]. Thereafter, Japanese institutes, including ours, have launched several real-world studies, which indicate the clinical benefits of optional first-line BEV for patients with severe clinical conditions [1,[6][7][8][9][10]. Practically, we selected first-line BEV for patients with unresectable GBM and accumulated the clinical data [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, there is no robust evidence supporting the efficacy of BEV treatment for nd-GBM; however, BEV has been approved in Japan as an insurance-covered first-line drug for GBM concurrently with its second-line application, considering the benefit of maintaining patient performance status [5]. Thereafter, Japanese institutes, including ours, have launched several real-world studies, which indicate the clinical benefits of optional first-line BEV for patients with severe clinical conditions [1,[6][7][8][9][10]. Practically, we selected first-line BEV for patients with unresectable GBM and accumulated the clinical data [11].…”
Section: Introductionmentioning
confidence: 99%
“…Glioblastoma (GBM) is one of the most common malignant brain tumors and has a poor prognosis. The current standard treatment for newly diagnosed GBM (nd-GBM) is maximal safe removal with concurrent temozolomide and radiation (TMZ-RT), followed by maintenance TMZ with, if possible, tumor-treating fields [ 1 ]. Despite such multimodal treatment, the median overall survival (OS) remains less than 2 years.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study demonstrated that BV was efficacious in patients with IDH1 wild type proneural glioblastoma [63], whereas it failed in some other treated patients [64]. Moreover, it has been reported that BV showed limited benefit on recurrent GBM, whereas it has no effects on the survival of patients with primary GBM [65,66]. This effect could be related to cells' epithelial-mesenchymal transition (EMT), responsible of drug-resistance and tumor relapse [67,68].…”
Section: Glioblastoma Multiforme: Classification Pathogenesis and Therapeutic Approachesmentioning
confidence: 99%
“…Upon recurrence, tumors may not enhance, secondary to vascular normalization. In addition, other recent prospective comparisons of Bevacizumab with other chemotherapeutic regimens have shown no signi cant increase in overall survival (OS) (14,15). The mechanisms of Bevacizumab failure are likely complex and multifactorial.…”
Section: Introductionmentioning
confidence: 99%